Cloud-Based Early Warning System for Forest Fire using IoT Techniques - Ramasamy, R Kanesaraj; Fang, Fang Chua; Gaik, Yee Chan (2018)
A forest fire is a national hazard which happens almost every year in Malaysia. Millions of Ringgit is used to save the life stocks and also the villagers around the affected areas. Although many traditional methods have been used to prevent the fire merely based on experience, no accurate plan is being implemented. Some systems are able to provide warning using historical data, but they are yet to provide an evacuation map. Hence, in this paper, we propose a cloud-based early warning system for a forest fire.The proposed system shall be able to provide warning to the firefighters before the fire starts. Additionally, it shall provide an evacuation plan for both the firefighters and also the villagers.Through the use of such a forest fire warning system coupled with an evacuation plan,life, property and environment damage could be reduced to a minimum